A comprehensive review of histopathological findings of infections induced by COVID-19 - Balaky, Salah Tofik Jalal; Zaki Abdullah, Sahar Mohammed; Alexander, Markov; Maashi, Marwah Suliman; Alkaim, Ayad F.; shahriyari, Sara; Tabari, Fariba; Kazemi, Elham (Cellular and Molecular Biology, 2020)
The severe acute respiratory syndrome (SARS)-Coronavirus (CoV2) virus, first identified in Wuhan, China, caused the coronavirus disease 2019 (COVID-19) which soon became a global pandemic, as labelled by the World Health Organization (WHO). The transmission method of the infection is primarily through droplets of various sizes. The SARS-CoV2 virus leads to a severe respiratory illness which in the first place causes the simulation of the acute respiratory syndrome. In order to diagnose of COVID-19 efficiently, samples with infection probability need to be examined through histopathological methods. Survival chances of the infected can remarkably increase if the virus is diagnosed timely by reverse transcription-polymerase chain reaction (RT-PCR) or computed tomography (CT) scan of the chest. One of the destructive effects of COVID-19 is the formation of ground-glass opacity (GGO) in the lungs which might be regarded to be equivalent to high-altitude pulmonary edema (HAPE). COVID-19 acts very similarly to SARS and Middle East Respiratory Syndrome (MERS) which can be inactivated by the chemical compounds of ethanol and sodium hypochlorite. Epidemiologic characteristics of COVID-19 have been indicated by numerous studies; however, there is still a lack of details of pathologic changes in the lung. The present comprehensive review is an attempt to assess and cover the current state of knowledge on COVID-19 disease based on the histopathologic studies conducted before May 2020.